Deep Reduced PEDOT Films Support Electrochemical Applications: Biomimetic Color Front - Martinez, Jose G.; Berrueco, Beatriz; Otero, Toribio F. (Frontiers in Bioengineering and Biotechnology, 2015)
Most of the literature accepts, despite many controversial results, that during oxidation/reduction films of conducting polymers move from electronic conductors to insulators. Thus, engineers and device’s designers are forced to use metallic supports to reoxidize the material for reversible device work. Electrochromic front experiments appear as main visual support of the claimed insulating nature of reduced conducting polymers. Here we present a different design of the biomimetic electrochromic front that corroborates the electronic and ionic conducting nature of deep reduced films. The direct contact PEDOT metal/electrolyte and film/electrolyte was prevented from electrolyte contact until 1cm far from the metal contact with protecting Parafilm®. The deep reduced PEDOT film supports the flow of high currents promoting reaction induced electrochromic color changes beginning 1 cm far from the metal-polymer electrical contact and advancing, through the reduced film, towards the metal contact. Reverse color changes during oxidation/reduction always are initiated at the film/electrolyte contact advancing, under the protecting film, towards the film/metal contact. Both reduced and oxidized states of the film demonstrate electronic and ionic conductivities high enough to be used for electronic applications or, as self-supported electrodes, for electrochemical devices. The electrochemically stimulated conformational relaxation (ESCR) model explains those results.